A Comparison of the Endoscopic and Histopathological Findings of Upper Gastrointestinal Mucosa with Helicobacter pylori infection - Gontar Alamsyah Siregar; Sumondang Pardede (The Indonesian Society for Digestive Endoscopy, 2003)
Helicobacter pylori infects the gastric mucosa or the duodenal wall undergoing gastric meteplasia, and is found in nearly 100% of chronic gastritis and duodenal ulcers. Helicobacter pylori produces urease that converts urea into ammonia, which will protect the organism from the acidic environment and will cause further damage to the gastrointestinal mucosa. Helicobacter pylori can be detected through histopathological evaluation, macroscopic endoscopy, serologic test, urea breath test, biopsy urease test, culture and stool analysis. Histiopathologically, Helicobacter pylori infection demonstrates neutrophil infiltration into the gastric mucosa, classified as focal infiltration. We conducted a prospective study of 50 chronic dyspeptic patients. We took their history, performed physical examinations, gastroscopy with judgement for macroscopic endoscopic appearance, histopathology from biopsy specimens, and the CLO test. There were 50 chronic dyspeptic patients in the study, with an age ranging from 23-81 years, and a mean age 49±12 year. Most of them were male (33 cases). There were 17 female cases. From the CLO test, there were 30 cases with CLO (+) and 20 cases CLO (-). From the 30 cases with CLO (+), 22 were male and 8 female. Gastroscopy revealed 25 cases of gastric ulcer, 7 duodenal ulcer, 2 gastric cancer, 15 gastritis, and 30 gastropathy. A gastroscopic appearance of chronic dyspepsia with positive Helicobacter pylori were found mostly in gastric ulcer (18 cases), followed by duodenal ulcer (6 cases), gastritis (5 cases) and one case of gastric cancer. A gastroscopic appearance of chronic dyspepsia with negative Helicobacter pylori were found mostly in gastritis 10 cases, while the remaining in gastric ulcer (7 cases), gastric cancer (2 cases), and a case of duodenal ulcer. Gastroscopy revealed 15 cases of gastritis. From the 5 gastritis cases with CLO (+), 3 cases had lesions located at the antrum and 2 cases at the corpus, while from the remaining 10 cases of gastritis with CLO (-), 8 cases had lesions located at the antrum, and 2 at the corpus. The time to colonization was shortest in duodenal ulcer (grade IV), followed by gastric ulcer (grade II) and gastritis (grade I) in CLO (-) examination. From cases of gastritis with CLO (+), 4 were moderate cases and one case severe, while from cases of gastritis with CLO (-) there were 7 mild cases, and 3 moderate cases with no severe case found. Keywords: Endoscopic findings, histopathology, Helicobacter pylori.